The Constraints of Management of Zakat and its Potensialin Poverty Reduction(Case study Medan City) - Siti Mujiatun, S.E., M.M. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The Constraints of Management of Zakat and its Potensialin Poverty Reduction(Case study Medan City)